PROVIDE A MODEL FOR MASS BEHAVIOR IN INVESTOR DECISION-MARKING IN INVESTMENT COMPANIES - Ardalan Rajabi, Ataullah Mohammadi Mlgrny, Mohsen Hamidiyan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The present study presents a model for mass behavior (derived from behavioral distortions) in the decision-making of investors in investment companies on the Tehran Stock Exchange. The methodology of this study is applied in terms of purpose, which initially after library and Gathering information about the factors affecting mass behaviors, experts in this field were consulted and these behavioral biases were scored. The statistical population of the present study in the qualitative phase includes experts of Tehran Stock Exchange. Eleven experts collaborated with the researcher in conducting specialized interviews. The results of the research indicate a model that company managers can, according to it and based on the weight of behavioral biases and the causes and intensity of mass behaviors and the cause of sudden market fluctuations. By improving the knowledge of behavioral financial factors; Managers of investment companies and other market analysts assist in identifying behavioral factors of market fluctuations. Finally, considering the significance of the whole model and also the significance of each coefficient of the final research model with 33 indicators and six main categories, which included self-control, perceptual error, social interactions, results, cognitive from an economic and judgmental point of view, respectively.